2017
DOI: 10.1007/s10822-017-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Binding free energy predictions of farnesoid X receptor (FXR) agonists using a linear interaction energy (LIE) approach with reliability estimation: application to the D3R Grand Challenge 2

Abstract: Computational protein binding affinity prediction can play an important role in drug research but performing efficient and accurate binding free energy calculations is still challenging. In the context of phase 2 of the Drug Design Data Resource (D3R) Grand Challenge 2 we used our automated eTOX ALLIES approach to apply the (iterative) linear interaction energy (LIE) method and we evaluated its performance in predicting binding affinities for farnesoid X receptor (FXR) agonists. Efficiency was obtained by our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…To start research in this direction, we have chosen the LIE method because it is computationally not expensive but still reliable in many cases. 11 13 , 15 , 18 , 40 42 Thus, the binding affinity of small molecules to six different proteins was studied using LIE. We found that in all cases, the correlation between the experimental and the simulation results is lower than that of JE, with the exception of MCL-1, where LIE ( R = 0.85) is slightly better than JE ( R = 0.83) ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To start research in this direction, we have chosen the LIE method because it is computationally not expensive but still reliable in many cases. 11 13 , 15 , 18 , 40 42 Thus, the binding affinity of small molecules to six different proteins was studied using LIE. We found that in all cases, the correlation between the experimental and the simulation results is lower than that of JE, with the exception of MCL-1, where LIE ( R = 0.85) is slightly better than JE ( R = 0.83) ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 − 9 The contribution from the electrostatic and van der Waals (vdW) interaction energy is obtained through the thermodynamic cycle. 10 In the past few decades, several groups have successfully applied the LIE method to predict new inhibitors of human dihydrofolate reductases 10 and to obtain the binding affinity of inhibitors of neuraminidase, 11 BACE-1, 12 cytochrome P450, 13 , 14 farnesoid X receptor, 15 and others. 16 Several improved versions of LIE were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Usually one is applied to the electrostatic interactions and one to the Lennard–Jones interactions. The extrapolation and use of interaction energies have led to the name Linear Interaction Energy, or LIE method [ 118 , 119 , 120 ]. For a thorough review of its theoretical basis, see [ 121 ].…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%
“…Another nuclear receptor, the farnesoid X receptor (FXR), was used as a test case for free energy calculations in 2018 [ 116 , 117 , 120 ]. FXR is involved in regulating bile acid, lipid, and glucose homeostasis [ 131 ], and it has been linked to hepatocarcinogenesis [ 132 ].…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%
See 1 more Smart Citation